Analysis of the application of polluted groundwater treatment technology using shell-based activated carbon media filters - Dedy Khaerudin; Ardi Hidayat (Jurnal Teknika, 2021)
One source of clean water used by residents of Sendal Kopo Subvillage, Panenjoan Village, Carenang District, Serang Regency comes from dug wells (groundwater), has a problem with very cloudy, yellow, sour taste and smells due to contamination from residual waste and the rest of the rice field irrigation system. The clean water treatment unit for community-based sanitation (Sanimas) owned by residents is no longer functioning by the central government. One alternative in treating polluted groundwater is to design a water filter installation from PVC pipes using activated carbon media from coconut shells and additional media for filter foam, injuk, zeolite stone, activated carbon, and silica sand to produce good raw water quality. Simple water analysis by making a water filter. The results of the analysis showed that the water content of activated carbon as the main medium was made after adding the activating agent ZnCl2, CaCl, or KCl 25% for 12-18 hours, indicating that the results met the SNI 06-3730-1995 regarding the standard of quality requirements and testing of activated charcoal both for water content <15% and ash content <10%, namely 7.56% and 7.89% ash content. The tool was tested on water samples ranging from color, pH, and Fe content from Panenjoan Village. After being tested using a water filter, the color of the water showed very good results. Initially, it was cloudy yellowish after passing through the filter to become clear white, while the pH test showed the results of 6.9 were still within the threshold because according to the regulation of the minister of health, No 492/Menkes/ Per/IV/2010 the pH is 6.5-8.5 while the level of Fe produced is 0.65 mg/l while according to the regulation it is 0.3 mg/l. Salah satu sumber mata air bersih yang digunakan warga Kp. Sendal Kopo, Desa Panenjoan, Kecamatan Carenang, Kabupaten Serang berasal dari sumur galian (air tanah), memiliki masalah dengan kondisi air sangat keruh, kuning, berasa asam dan berbau akibat berasal dari pencemaran beberapa limbah dan sisa sistem pengairan sawah. Unit pengolahan air bersih sanitasi berbasis masyarakat (Sanimas) yang dimiliki warga sekitar sudah tidak berfungsi dari pemerintah pusat. Salah satu alternatif dalam pengolahan air tanah yang tercemar dengan mendisain instalasi filter air dari pipa PVC menggunakan media carbon aktif dari tempurung kelapa dan media tambahan busa filter, injuk, batu zeloit, carbon aktif dan pasir silika agar menghasilkan kualitas air baku yang baik. Analisis air sederhana dengan membuat filter air. Hasil analisis menujukan kadar air carbon aktif sebagai media utama yang di buat setelah menambahkan agen aktivator ZnCl2, CaCl atau KCl 25% selama 12-18 jam menujukan hasil memenuhi syarat standar SNI 06-3730-1995 tentang standard syarat mutu dan pengujian arang aktif baik untuk kadar air < 15% dan kadar abu <10%. yaitu 7,56 % dan kadar abu 7,89%. Alat tersebut di uji terhadap sample air mulai dari warna, pH, dan kadar Fe dari Desa Panenjoan. Warna air setelah di uji dengan menggunakan filter air menujukan hasil yang sangat baik, semula berwaran keruh kekuningan setelah melewati filter menjadi putih bening, sedangkan pengujian pH menunjukan hasil 6,9 masih dalam ambang batas karena menurut peraturan menteri kesehatan, No. 492/Menkes/Per/IV/2010 pH sebesar 6,5-8,5 sedangkan kadar Fe yang dihasilkan 0,65 mg/l sedangkan menurut peraturan yaitu 0,3 mg/l.